Histological characterization of interneurons in Alzheimer's disease reveals a loss of somatostatin interneurons in the temporal cortex. Issue 4 (30th March 2020) - Waller, Rachel; Mandeya, Memory; Viney, Edward; Simpson, Julie E.; Wharton, Stephen B.
Abstract : Neuronal dysfunction and synaptic loss are major hallmarks of Alzheimer's disease (AD) which correlate with symptom severity. Impairment of the γ‐aminobutyric acid (GABA)ergic inhibitory interneurons, which form around 20% of the total neuronal network, may be an early event contributing to neuronal circuit dysfunction in neurodegenerative diseases. This study examined the expression of two of the main classes of inhibitory interneurons, parvalbumin (PV) and somatostatin (SST) interneurons in the temporal cortex and hippocampus of AD and control cases, using immunohistochemistry. We report a significant regional variation in the number of PV and SST interneurons with a higher number identified per mm 2 in the temporal cortex compared to the hippocampus. Fewer SST interneurons, but not PV interneurons, were identified per mm 2 in the temporal cortex of AD cases compared to control subjects. Our results support regional neuroanatomical effects on selective interneuron classes in AD, and suggest that impairment of the interneuronal circuit may contribute to neuronal dysfunction and cognitive decline in AD.